Not the only game in towns: explaining changes in municipal councils in post-revolutionary Tunisia. Issue 8 (17th November 2019) - Clark, Janine A.; Dalmasso, Emanuela; Lust, Ellen
ABSTRACT: This study sheds light on the relationship between local and national elites during political transitions. Examining local councils in post-revolutionary Tunisia (2011–2013), it examines why and when the composition of councils changed in the absence of local elections. The study yields two important lessons. First, changes in councils resulted from a power struggle between national and local elites. Councils were more likely to remain in place when local parties and unions helped council members resist pressures from above. The interplay of local and national actors, and not the council's competencies, explains when changes took place. Second, all councils became politicized in the process. Far from being caretaker councils impartially addressing local needs, the councils were institutions playing important roles in the struggles between local and national political elites. Councils were arenas in which political power, and notions of legitimate representation, were contested in the absence of elections. The argument is supported by quantitative analyses of original data and four comparative case studies based on qualitative fieldwork. The findings highlight the importance of local councils in transition processes and provide a basis for further work exploring local-national engagement in democratization.